Avaliação de parâmetros físico-químicos e microbiológicos de água subterrânea na comunidade ribeirinha Costa da Conceição - Mota, Alice Farias de Souza (Brasil, 2023)
The Amazon region, despite having the largest hydrographic basin in the world, populations suffer from problems related to good quality water. With this, the present research aims to evaluate the quality of groundwater from the well of the riverside community of Costa da Conceição, analyzing the organoleptic parameters (odor, taste and appearance), physicochemical (pH, electrical conductivity, temperature, turbidity, salinity, suspended solids, total suspended solids, apparent color, real color, nitrite, nitrate, ammonia and phosphate), and microbiological (coliforms and Escherichia coli). The organoleptic analyzes were carried out through the sensory organs. The physical-chemical parameters were obtained through the following methodologies: electrometry, turbidimetry, photometry and gravimetry. Microbiological parameters were determined qualitatively using COLITEST®. The collected data were interpreted and compared with Ordinance MS nº 888/21 to obtain the water quality in advance. The results of this research evidenced a difference in the concentration values of the constituents in solution if we compare the dry and wet periods. Turbidity, apparent color and ammonia were out of the established standard, as well as for the microbiological analyses, a situation that classifies this water as unfit for human consumption, highlighting the need for basic sanitation in the community.